IMPLEMENTASI PEMBELAJARAN DISTANCE LEARNING DALAM MATA PELAJARAN GEOGRAFI DI SMA NEGERI 8 PADANG - Sarifah Aini Aini; Syafri Anwar (JURNAL BUANA, 2022)
This study aims to determine the implementation of distance learning and its obstacles and solutions in geography subjects at SMA Negeri 8 Padang. Descriptive qualitative research methods with data collection techniques by observation, interviews and documentation. Data analysis techniques by reducing, presenting and providing conclusions. The results of the study were (1) The implementation of distance learning in geography subjects was carried out online from home using the google classroom application and whatsapp group (2) The obstacles encountered were students having limited learning resources, networks, internet quotas so that it had an impact on understanding of the material and aspects of teachers who had difficulty in delivery. material, it is difficult to know the pedagogic and social abilities of students online then supervision of students is difficult and (3) Schools conduct IHT (In House Training) and seminars on online learning applications used in distance learning, then for students who are constrained by networks and quotas are allowed send assignments at a specified time or face to face at school.